Research on the Intelligent Display of Cultural Relics in Smart Museums Based on Intelligently Optimized Digital Images. (15th December 2021) - Sha, Yutian; Zhang, Shaohan; Feng, Tianxin; Yang, Ting
Abstract : The smart museum is a new platform for the appreciation and display of cultural relics across time and space. In the era of 3D scanning technology, computer technology, and network technology, it is necessary to deeply study the smarter and more perfect forms of smart museums. This article, through the analysis of the characteristics of the display level of the smart museum, tries to create a new humanized and intelligent display of cultural relics.